Integration of local mean sea level and land vertical datum over peninsular Malaysia via transformation model - Pa’suya, Muhammad Faiz; Md Din, Ami Hassan; Ramazan Alpay, Abbak; Talib, Noorfatekah; Che Aziz, Mohamad Azril; Bin Ramli, Muhammad Zahir; Hamden, Mohammad Hanif; Mohammad Yazid, Nornajihah (Birkhauser, 2024)
Integration of land and marine vertical datums is an important aspect of geospatial reference systems. Therefore, this study has been conducted to identify an optimum approach to integrate the marine and land vertical datums. Two hybrid geoid models have been developed and fitted to the the land levelling datum at benchmark and to the tide gauge-benchmark station (TGBM). The differences between the two hybrid geoid models were computed to establish a vertical datum transformation model (VDT). Among the 305 GNSS-levelling points, 295 have been used in the hybridization process and 10 have been used for validation. Based on the comparison, the geoidal differences at the 10 points range from -7.2 to 7.0 cm while the mean and RMSE of differences are 1.3 cm and ± 4 cm, respectively. The second hybrid geoid, which was fitted to local MSL, was developed by directly adding to the offset between the gravimetric geoid and local MSL at nine TGBM stations. The result indicates that the offset derived at Tanjung Gelang is the optimum one with an RMSE of ±0.045 m. The VDT model developed shows a transformation accuracy of approximately ± 4 cm.